A Systematic Review of Human Challenge Trials, Designs, and Safety. (11th October 2022) - Adams-Phipps, Jupiter; Toomey, Danny; Więcek, Witold; Schmit, Virginia; Wilkinson, James; Scholl, Keller; Jamrozik, Euzebiusz; Osowicki, Joshua; Roestenberg, Meta; Manheim, David
Abstract: Background: Few studies have assessed participant safety in human challenge trials (HCTs). Key questions regarding HCTs include how risky such trials have been, how often adverse events (AEs) and serious adverse events (SAEs) occur, and whether risk mitigation measures have been effective. Methods: A systematic search of PubMed and PubMed Central for articles reporting on results of HCTs published between 1980 and 2021 was performed and completed by 7 October 2021. Results: Of 2838 articles screened, 276 were reviewed in full. A total of 15 046 challenged participants were described in 308 studies that met inclusion criteria; 286 (92.9%) of these studies reported mitigation measures used to minimize risk to the challenge population. Among 187 studies that reported on SAEs, 0.2% of participants experienced at least 1 challenge-related SAE. Among 94 studies that graded AEs by severity, challenge-related AEs graded "severe" were reported by between 5.6% and 15.8% of participants. AE data were provided as a range to account for unclear reporting. Eighty percent of studies published after 2010 were registered in a trials database. Conclusions: HCTs are increasingly common and used for an expanding list of diseases. Although AEs occur, severe AEs and SAEs are rare. Reporting has improved over time, though not all papers provide a comprehensive report of relevant health impacts. We found very few severe symptoms or SAEs in studies that reported them, but many HCTs did not report relevant safety data. This study was preregistered on PROSPERO as CRD42021247218. Abstract : A systematic review of health risks in human challenge trials published between 1980 and 2021 found no reported deaths or cases of permanent damage. Of challenged participants, 0.2% experienced serious adverse events and no deaths were observed.